Fabrication and testing of a newly designed slit system for depth‐resolved X‐ray diffraction measurements. (6th October 2016) - Sinsheimer, John; Bouet, Nathalie; Ghose, Sanjit; Dooryhee, Eric; Conley, Ray
Abstract : A newly designed system of slits for depth‐resolved X‐ray powder diffraction has been developed and tested at the National Synchrotron Light Source. Abstract : A new system of slits called `spiderweb slits' have been developed for depth‐resolved powder or polycrystalline X‐ray diffraction measurements. The slits act on diffracted X‐rays to select a particular gauge volume of sample, while absorbing diffracted X‐rays from outside of this volume. Although the slit geometry is to some extent similar to that of previously developed conical slits or spiral slits, this new design has advantages over the previous ones in use for complex heterogeneous materials and in situ and operando diffraction measurements. For example, the slits can measure a majority of any diffraction cone for any polycrystalline material, over a continuous range of diffraction angles, and work for X‐ray energies of tens to hundreds of kiloelectronvolts. The design is generated and optimized using ray‐tracing simulations, and fabricated through laser micromachining. The first prototype was successfully tested at the X17A beamline at the National Synchrotron Light Source, and shows similar performance to simulations, demonstrating gauge volume selection for standard powders, for all diffraction peaks over angles of 2–10°. A similar, but improved, design will be implemented at the X‐ray Powder Diffraction beamline at the National Synchrotron Light Source II.